Salivary Iga Depression In Drug-influenced Gingival Enlargement Among Hypertensive Patients - Muhammad Annurdin Sabarudin; Haslina Taib; Wan Majdiah Wan Mohamad; Siti Lailatul Akmar Zainuddin; Wan Syamimee Wan Ghazali (Faculty of Dentistry Universitas Indonesia, 2024)
Indexed by WOS